GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Prita Karina Diandra (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to examine the relationship and influence by using the independent variables, namely, good corporate governance which is proxied by institutional ownership with independent commissioners and disclosure of corporate social responsibility on firm value. The company value variable is measured using Tobin's Q, CSR disclosure variable is measured using the GRI G4 index. This study uses secondary data, namely annual reports, financial reports and sustainability reports. The sample used is manufacturing companies in the basic industry and chemicals sub-sector which are listed on the Indonesia Stock Exchange for the 2016-2018 period. The total sample selected was 138. The sampling technique used was purposive sampling. The method used in this study is multiple linear regression analysis. The results of the analysis of this study indicate that the good corporate governance variable which is proxied by institutional ownership has a negative effect on firm value while the independent commissioners have no effect on firm value and the CSR disclosure variable has a positive effect on firm value